Comparing outcomes between culture-positive and culture-negative septic shock in a PICU: A retrospective cohort study - Huang, Haixin; Chen, Jian; Dang, Hongxing; Liu, Chengjun; Fu, Yue-qiang (Frontiers in Pediatrics, 2022)
Background We assessed the outcomes and characteristics of culture-negative septic shock (CNSS) and culture-positive septic shock (CPSS) in pediatric intensive care unit (PICU). Methods We performed a retrospective study on the data of children admitted to the PICU due to septic shock between January 2018 and December 2021. The primary outcome was in-hospital mortality. The secondary outcomes were the length of stay (LOS) of hospital, the need for mechanical ventilation (MV) and continue renal replacement therapy (CRRT). Results Overall, 238 patients were enrolled. 114 patients (47.9%) had positive cultures (60 blood samples, 41 sputum samples, 17 pus samples, and 19 others), 18 of whom were cultured positive at two sites, 1 at three sites, and 3 had two different types of bacteria at same site. The in-hospital mortality was 47.1%. There were no significant differences in the in-hospital mortality (47.6% vs. 46.5%, P = 0.866), PRISM-III score (10 vs. 12, P = 0.409), PIM-3 score (0.08 vs. 0.07, P = 0.845), pSOFA score (10 vs. 10, P = 0.677) or the need for MV (64.5% vs. 68.4%, P = 0.524) and CRRT (29.8% vs. 34.2%, P = 0.470) between the CNSS group and the CPSS group. The Procalcitonin (8.89 ng/ml vs. 28.39 ng/ml, P = 0.001) and C-reactive protein (28 mg/L vs. 58 mg/L, P = 0.001) levels were significantly lower in the CNSS group than in the CPSS group, while WBC count (9.03 × 109/L vs. 5.02 × 109/L, P = 0.002) and serum sodium (137 mmol/L vs. 132 mmol/L, P = 0.001) was significantly higher in CNSS. The LOS of hospital was significantly longer (16 days vs. 11 days, P = 0.011) in the CPSS group than in the CNSS group, while the LOS of PICU (5 days vs. 4 days, P = 0.094) stay was not significantly different. Conclusion Compared with children with CNSS, children with CPSS had higher PCT and CRP levels, but lower WBC count. Children with CPSS had longer LOS of hospital. However, positive or negative culture results were not associated with in-hospital mortality, the LOS of PICU, the need for MV or CRRT in children with septic shock.